1994
DOI: 10.1086/187523
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency spectra of gamma-ray bursts

Abstract: Particles with energies below the mean energy E 0 in relativistic shocked plasmas should assume an equilibrium energy distribution. This leads to a synchrotron spectrum F ν ∝ ν 1/3 up to approximately the critical frequency ν 0 of an electron with the energy E 0 . Application to GRBs implies that a burst with 10 −5 erg/cm 2 s of soft gamma-rays and hν 0 = 300 KeV should be about 18th magnitude in visible light and a few µJy at 1 GHz (less if self-absorbed).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
222
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 261 publications
(236 citation statements)
references
References 23 publications
14
222
0
Order By: Relevance
“…• verify the strongest prediction of the synchrotron theory of a low energy spectral shape not evolving and fixed to −2/3 (Katz et al 1994). For clarity we first present the results for the time integrated (Sect.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…• verify the strongest prediction of the synchrotron theory of a low energy spectral shape not evolving and fixed to −2/3 (Katz et al 1994). For clarity we first present the results for the time integrated (Sect.…”
Section: Resultsmentioning
confidence: 58%
“…Alternative spectral models -and in particular the predictions for synchrotron emission (Katz 1994;Crider et al 1997a,b) -have also been recently tested on a large sample of time resolved spectra by Preece and collaborators (Preece et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The gamma-ray burst GRB 970228 [1,2] has been observed after a delay of [8][9][10][11][12][13][14][15][16][17] hours in x rays [3] and of 17 hours in visible light [4]. This marks the first detection of emission at lower frequencies following the gamma-ray observation of a gamma-ray burst (GRB) and the first detection of any visible counterpart to a GRB.…”
mentioning
confidence: 99%
“…It also leads to a specific prediction for its spectrum, which may be roughly tested with the data at hand. The instantaneous spectrum of a relativistic shock is predicted [15,16] to be F n~n 1͞3 . The spectrum integrated over the radiative decay of the electrons' energy is predicted [17] to be F n~n 21͞2 .…”
mentioning
confidence: 99%
“…The discovery of GRB afterglow emission in X-ray (Costa et al 1997), optical (van Paradijs et al 1997) and radio wavelengths (Frail et al 1997) confirmed (Waxman 1997, Wijers, Rees & Mészáros 1997, standard model predictions of afterglow (Paczyński & Rhoads 1993, Kats 1994, Vietri 1997) that results from the collision of the expanding fireball with surrounding medium.…”
Section: Introductionmentioning
confidence: 94%